2017
DOI: 10.3389/fpsyg.2017.01257
|View full text |Cite
|
Sign up to set email alerts
|

Seven Years Cognitive Functioning and Early Assessment in Extremely Low Birth Weight Children

Abstract: Infants born preterm are at high risk for the onset of cognitive dysfunctions at school age. The aim of this study was to investigate the association between early neurodevelopmental assessment and the risk of adverse cognitive outcome in extremely low birth weight children. We enrolled all newborns (January 2002 – April 2007) consecutively admitted to our Institution, with a birthweight < 1000 g. Exclusion criteria were genetic abnormalities, severe neurofunctional impairment, and/or neurosensory disabilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 44 publications
(45 reference statements)
0
19
0
Order By: Relevance
“…Some research has been performed on the value of the GMDS for predicting later developmental problems. Squarza et al conducted a study on early developmental level and cognitive outcomes in 99 children with an extremely low birth weight, and the results showed that the lower the GMDS score was at 1 year, the more severe the cognitive impairment was at school age, indicating a high predictive power of the GMDS 29. This predictive power increased with increasing age at assessment 17,18.…”
Section: Discussionmentioning
confidence: 99%
“…Some research has been performed on the value of the GMDS for predicting later developmental problems. Squarza et al conducted a study on early developmental level and cognitive outcomes in 99 children with an extremely low birth weight, and the results showed that the lower the GMDS score was at 1 year, the more severe the cognitive impairment was at school age, indicating a high predictive power of the GMDS 29. This predictive power increased with increasing age at assessment 17,18.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical relevance of these short-term results needs to be confirmed later in childhood when neurobehavioral and cognitive impairments become more obvious, although studies on the neurodevelopmental trajectories of preterm infants have suggested the predictive value of the 12 months' assessment on long-term outcomes (69).…”
Section: Discussionmentioning
confidence: 99%
“…We further demonstrate that the Early Intervention program enhances neurodevelopment at 12 months corrected age compared to Standard Care, albeit scores are within the normal range for both groups. The clinical relevance of these short-term results needs to be confirmed later in childhood when neurobehavioral and cognitive impairments become more obvious, although studies on the neurodevelopmental trajectories of preterm infants have suggested the predictive value of the 12 months’ assessment on long-term outcomes (69).…”
Section: Discussionmentioning
confidence: 99%
“…mild cognitive delay, learning disabilities) and behavioral (i.e. autism, hyperactivity) impairments 3,4 .…”
mentioning
confidence: 99%